YouTube, Public Discourse, and the ‘Makan Siang Gratis’ Program: An Analysis of Toxicity Comments on the Liputan6 Channel - Jayus, Jayus; Abdullah, Assyari; Mustafa, Mustafa; Sumaiyah, Sumaiyah (Jogjakarta Communication Conference (JCC), 2025)
This study investigates the toxicity of comments on the ‘Makan Siang Gratis’ Program features on the Liputan6 YouTube Channel. Using the Toxicity Comment Analysis Method, the study aim to identify, measure, and understand the level of toxicity in user comments. Data were collected through the Communalytic platform, which facilitates automated data retrieval from the official YouTube API. This tool was used for comment scraping, which was then analyzed using the toxicity analysis feature to obtain toxicity scores based on indicators such as the severity of comments, hate speech, target identity, and threats contained within the comments. The findings show that while most comments had low toxicity scores, some comments exhibited higher levels of toxicity, particularly in the categories of severe toxicity and profanity. Comments with higher toxicity scores have the potential to disrupt constructive conversations and create polarization among user, diminishing the quality of interactions. Several toxicity, although rare, tends to trigger strong emotional responses, escalate conflicts, and lower the overall quality of discourse. Similarly, profanity and insults reduce the inclusivity of discussions, causing some users to refrain from participating. Identity attacks, though infrequent, can target individuals based on their characteristics and threaten the diversity of opinions in discussions. This study underscores the importance of moderation to manage toxic comments and maintain an online space that is respectful and inclusive.